A neurological presentation caused by brain metastases in a dog with interventricular septal hemangiosarcoma. Issue 4 (13th January 2021) - Bunn, TA; Robveille, C; Irwin, PJ; Langner, KFA
Abstract : Background: Brain metastases are well known for disseminated hemangiosarcoma involving the right atrium/auricle. Case report: An 8‐year‐old male Australian Shepherd Dog presented with a 3‐day history of circling to the left. A neurological examination revealed obtunded mentation, right hemi‐inattention, bilateral strabismus towards the left side and absent physiological nystagmus. In addition, the dog had muffled heart sounds on auscultation and exercise‐induced weakness. Laboratory findings included hypercoagulability and marked elevation in the C‐reactive protein concentration. Electrocardiography detected a sinus rhythm with right bundle‐branch block and ventricular bigeminy. Echocardiography revealed an extensive interventricular septal mass. Due to the grave prognosis, the owners elected for euthanasia, and a complete necropsy was performed. The main pathological findings were an interventricular septal and left ventricular hemangiosarcoma, with metastases in the brain, lungs, spleen and adrenal glands. No evidence of tumour infiltration was found in the right atrium. Conclusion: To the authors' knowledge, this is the first report of neurological signs due to confirmed brain metastases in a dog with interventricular septal hemangiosarcoma. Although the right atrium is the main location for cardiac hemangiosarcoma, the interventricular septum should be evaluated in all cases.